2019
DOI: 10.1038/s41598-019-39971-z
|View full text |Cite
|
Sign up to set email alerts
|

Transmission dynamics study of tuberculosis isolates with whole genome sequencing in southern Sweden

Abstract: Epidemiological contact tracing complemented with genotyping of clinical Mycobacterium tuberculosis isolates is important for understanding disease transmission. In Sweden, tuberculosis (TB) is mostly reported in migrant and homeless where epidemiologic contact tracing could pose a problem. This study compared epidemiologic linking with genotyping in a low burden country. Mycobacterium tuberculosis isolates (n = 93) collected at Scania University Hospital in Southern Sweden were analysed with the standard geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
3
17
2
Order By: Relevance
“…Our findings confirm the homoplasy described before in MIRU-VNTR typing, particularly for the Beijing lineage (Alaridah et al, 2019;Gurjav et al, 2016;Nikolayevskyy, Kranzer, Niemann, & Drobniewski, 2016), revealed by the high discriminatory power of WGS, as described for other settings (Gardy et al, 2011;Stucki et al, 2016). Moreover, our data allows to suggest that the Beijing A strain has probably been present for a long time, with only a minority of cases due to recent transmission.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings confirm the homoplasy described before in MIRU-VNTR typing, particularly for the Beijing lineage (Alaridah et al, 2019;Gurjav et al, 2016;Nikolayevskyy, Kranzer, Niemann, & Drobniewski, 2016), revealed by the high discriminatory power of WGS, as described for other settings (Gardy et al, 2011;Stucki et al, 2016). Moreover, our data allows to suggest that the Beijing A strain has probably been present for a long time, with only a minority of cases due to recent transmission.…”
Section: Discussionsupporting
confidence: 91%
“…Another study from Hawaii reported 24-loci MIRU-VNTR typing has specificity of 28.6% for identifying actual transmission clusters, and this traditional typing has poor performance especially when identifying transmission in Beijing and Manila family clusters [21]. Contrary to traditional genotyping methods, WGS Provides detailed insights into transmission dynamics [22,23]. Study in low TB incidence setting showed that WGS provides better correlation with epidemiologic data than MIRU-VNTR typing [23].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to traditional genotyping methods, WGS Provides detailed insights into transmission dynamics [22,23]. Study in low TB incidence setting showed that WGS provides better correlation with epidemiologic data than MIRU-VNTR typing [23]. Previous studies have indicated that MIRU-VNTR typing may overestimate recent TB transmission, particularly in regions with high TB incidence settings [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Notice the connection with the minimum correlation clustering problem: solving the minimum consensus problem for a given set of clusterings π (1) , . .…”
Section: Consensus Clusteringmentioning
confidence: 99%
“…the alleles at a small number of pre-specified housekeeping genes) [23] have been the predominant mode of genotyping bacterial pathogens. These low-resolution signals, which we may refer to as "fingerprints", could lead to incorrectly clustered strains [1] since unrelated bacterial isolates may happen to share identical fingerprints. With the advent of next-generation sequencing (NGS) [22], new genotypic signals have become available.…”
Section: Introductionmentioning
confidence: 99%